Macroeconomic vulnerability in developing countries: Approaches and issues - Anuradha Seth; Amr Ragab (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
Economic vulnerability is approached from micro- and macroeconomic perspectives. While the microeconomic perspective is concerned with the impact of shocks on the well-being of individual households, the macroeconomic perspective focuses on the impact of these shocks on economic growth. This paper reviews the literature on macroeconomic vulnerability and finds that there is no single approach to understanding macroeconomic vulnerability in the context of financial and economic crises in developing countries. It identifies the critical contributions of different studies on macroeconomic vulnerability and appraises their main differences. The paper then proposes elements for a more comprehensive framework of macroeconomic vulnerability for developing countries. In a world where shocks and crises are becoming more frequent, the imperative for countries to build resilience and protect themselves from development reversals has become all the more urgent. Not surprisingly, addressing macroeconomic vulnerability has become an important aspect of the international development agenda.
Keywords: 330; vulnerability; resilience; macroeconomic; growth; Wirtschaftswachstum; Schock; Entwicklungsländer